2004
DOI: 10.1902/jop.2004.75.9.1209
|View full text |Cite
|
Sign up to set email alerts
|

Relative Proportions of T‐Cell Subpopulations and Cytokines That Mediate and Regulate the Adaptive Immune Response in Patients With Aggressive Periodontitis

Abstract: These results indicate that the role of the CD8+ subpopulation in aggressive periodontitis lesions is limited. On the other hand, cytokines IL-2 and IFN-gamma may not be relevant in the progression of aggressive periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…This interleukin is critical in the initiation and progression of periodontal inflammatory [27, 28]. Clinical researches have shown that IL-10 levels in GCF are lower in periodontitis sites, whereas the expression in healthy sites is higher [29]. Furthermore, alveolar bone loss is reportedly significant in IL-10 knockout mice [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…This interleukin is critical in the initiation and progression of periodontal inflammatory [27, 28]. Clinical researches have shown that IL-10 levels in GCF are lower in periodontitis sites, whereas the expression in healthy sites is higher [29]. Furthermore, alveolar bone loss is reportedly significant in IL-10 knockout mice [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mRNA expression of IL‐13 was determined in T cells extracted from gingival biopsies from patients with aggressive periodontitis, gingivitis and healthy controls. IL‐13 was only detected in the gingivitis and healthy groups (Suarez et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1B). Several studies reported significantly higher IL-10 expression that was often associated with nondiseased, treated, and healthy periodontal tissues or gingivitis (9,10,24). It is clear that in both cases, there was no alveolar bone loss or active disease progression in vivo; however, we cannot be certain whether the cytokine regulatory mechanisms in welltreated periodontal tissues are the same or similar to those in IL-10-treated mice.…”
mentioning
confidence: 83%